Application of the Problem Based Learning (PBL) Model on Environmental Pollution Materials to Increase Motivation and Learning Outcomes - Indri Pratiwi; Yoyon Sutresna; Nina Helina (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
Motivation to learn is an encouragement both from outside and from within a person to develop interest, desire, and ability to learn and acquire new knowledge. The existence of high motivation is very important to determine success in the learning process of students. This study aims to analyze the increase in motivation and learning outcomes in natural sciences on environmental pollution through the Problem Based Learning. Methods of data collection using questionnaires, interviews, observations and tests. Implementation of this research three cycles, each cycle of activities are: planning, implementation, observation, and reflection. The results of the action research cycle I average value of learning motivation included in the sufficient category. The results of the action research cycle II mean value of learning motivation included in the sufficient category. The final results of the action in the third cycle the average value of learning motivation included in the high category. These results have exceeded the indicators of success, students so that the application of the Problem Based Learning model for 3 cycles to the motivation and learning outcomes of students experienced increase.